Creativity Of English Tutorial Activities In Helping Students Understanding Online Learning In Elementary School - Nuradi, Farah Zafiroh; Kurniawati, Elisa; Faizah, Nur; Rachmawati, Umi (Prosiding University Research Colloquium, 2021)
Because the covid-19, learning that was originally at school has now become home through the online system. Online learning has various limitations, for example, the absence of gadget facilities (cell phones and laptops), low understanding of digital media and limited signal. Students who usually study in class and are explained directly to the teacher, now the teacher only gives reading explanations and gives assignments, this makes students more confused because there is no clear explanation but are forced to understand by doing assignments. This study uses descriptive qualitative research that describes tutoring services in reducing difficulties in student learning during the COVID-19 period. Students always ask to be helped with assignments. Students need assistance in learning, so that the material can be easily understood optimally.